ДИАБЕТИЧЕСКАЯ АВТОНОМНАЯ КАРД ИАЛЬНАЯ НЕЙРОПАТИЯ У БОЛЬНЫХ САХАРНЫМ ДИАБЕТОМ 2 ТИПА: ФОКУС НА НЕРЕШЁННЫЕ ПРОБЛЕМЫ - М. Е. Стаценко; С. В. Туркина (Архивъ внутренней медицины, 2013)
It is well known that cardiac autonomic neuropathy (CAN) is the negative prognostic factor which increases mortality in patients with diabetes mellitus. CAN may have greater predictive power for cardiovascular events than traditional risk factors. Significant morbidity and mortality can now be attributable to autonomic imbalance between the sympathetic and parasympathetic nervous system regulation of cardiovascular function. This review covers the epidemiology, pathophysiology, clinical presentation, and diagnosis of CAN in diabetes and discusses current evidence on approaches to prevention and treatment of CAN.